Paraguay : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1999)
This report describes economic developments in Paraguay during the 1990s. Despite a severe banking crisis, the macroeconomic performance in 1995 was relatively good as real GDP growth picked up to 4.2 percent from 3.1 percent in 1994. Inflation fell to 10.5 percent by end-1995, compared with 18.3 percent at end-1994. Still, the economy was weakened, as a credit crunch arising from the problems in the financial sector and decreased activity in Paraguay's re-export trade took their toll.